2020
DOI: 10.1016/j.scitotenv.2020.136780
|View full text |Cite
|
Sign up to set email alerts
|

Litter and soil biogeochemical parameters as indicators of sustainable logging in Central Amazonia

Abstract: One-fourth of Brazilian Amazonia is managed for timber production, but only a few logging sites follow sustainable forest management plans (SFMPs). Amazon forests without SFMPs are susceptible to deforestation because such plans integrate the use of forest products and conservation goals by allowing selective wood extraction following regulations. It remains uncertain whether reduced-impact selective logging (17-20 m 3 ha − 1 yr − 1 of 38-70 species), typical of SFMPs, changes forest regeneration, carbon (C) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…We found an association between leaf fall and the Formicidae group, both high in the dry season. We believe that this relates to Formicidae's high mobility and that several species in this family inhabit the leaf litter layer (Bomfim et al, 2020;Nunes et al, 2021). Also, these authors found that most ant species live in the leaf litter, and only a small part of the species lives in the twigs litter.…”
Section: Relationships Between Litterfall and Soil Epigeic Faunamentioning
confidence: 85%
See 1 more Smart Citation
“…We found an association between leaf fall and the Formicidae group, both high in the dry season. We believe that this relates to Formicidae's high mobility and that several species in this family inhabit the leaf litter layer (Bomfim et al, 2020;Nunes et al, 2021). Also, these authors found that most ant species live in the leaf litter, and only a small part of the species lives in the twigs litter.…”
Section: Relationships Between Litterfall and Soil Epigeic Faunamentioning
confidence: 85%
“…As one of the world's hotspots for biodiversity conservation, the Cerrado has high species endemism, heterogeneity of landscapes, and faces rampant human threat (Morandi et al, 2018;Myers et al, 2000;Strassburg et al, 2020); between 2008 and 2012, annual deforestation rates were twice as those in the Brazilian Amazon (Lambin et al, 2013). Also, less than half of the original land covered by Cerrado ecosystems is still conserved (Zuin, 2020), which jeopar-dizes their role in the water and carbon cycles (Arantes et al, 2016;Brasil, 2018). Reducing greenhouse gas emissions by avoiding deforestation can provide a monetary incentive through REDD+ initiatives in Cerrado areas (Gallo and Albrecht, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Logging effects on SOC stocks topsoil can be direct and indirect; tree removal directly reduces OM input to the soil, and indirectly affects decomposition rate, modifying litter quality and microsite conditions (Pérez-Suárez et al 2012). Logging modi es litter quality input to the soil by creating canopy gaps that promote secondary succession in the understory, i.e., it increases the presence of easily decomposable herbs and shrubs (less recalcitrance), limiting SOM pools (Cepáková and Frouz 2015;Bom m et al 2020). Microsite conditions are also altered when canopy gaps increase the light incidence and temperature on the forest oor (Coletta et al 2017;Bom m et al 2020).…”
Section: Main Drivers Of Soc Stocks On Mountain Forest Soils From the Nevado De Tolucamentioning
confidence: 99%
“…In the Atlantic Forest, where secondary forests are dominated by fast-growing and wood-producing species, with a rapid increase in timber stocks in the early stages of succession, commercial species represent about 51 percent of tree diversity. Such commercial species over 15 cm in diameter appear after 20 years of regrowth, with trees over 30 cm 10 years later [45,46].…”
Section: Woody Species Recoverymentioning
confidence: 99%